Ibuk Plandi : Pemanfaatan Tanaman Obat Keluarga (TOGA) menjadi Produk Bumbu Instan Bubuk dalam Membangun Ecopreneur Ibu PKK Desa Plandi Kabupaten Malang - Elsa Lutfiyah; Fauziyatul Khoiroh; Hafizh Naufalian; Sri Untari (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
Plandi village is located in Wonosari sub-district, Malang district, East Java, in a mountainous area far from Malang city. In an effort to improve the welfare of the community, a PKK organisation was formed in Plandi Village which aims to empower women through positive activities such as social activities and economic development. Based on observations, the activities of PKK mothers in Plandi Village are still not optimal because there are no activities that can increase family income. Through the student service programme, a solution is proposed in the form of utilising family medicinal plants (TOGA) into powdered instant seasoning products that have high selling value. The implementation of the programme includes socialisation, entrepreneurship assistance and demonstration of product making. In addition to producing ‘ibuk plandi’ products, the results of implementing this programme are an increase in the knowledge and skills of PKK mothers in processing TOGA and ecopreneur.